INFLUENCE OF MINERAL ACCRETION INDUCED BY ELECTRIC CURRENT ON THE SETTLEMENT AND GROWTH OF THE SCLERACTINIAN CORAL POCILLOPORA DAMICORNIS (CNIDARIA, ANTHOZOA, HEXACORALLIA) - Chavanich, Suchana; Ussavauschariyakul, Siriwan; Viyakarn, Voranop; Fujita, Toshihiko (Marine Research in Indonesia, 2013)
The effect of mineral accretion induced by electric current on settlement, growth, and survival of planula larvae and juvenile corals of Pocillopora damicornis was examined by both laboratory and field experiments. The laboratory experiment showed that the numbers of larvae settling on tiles with coralline algae and steel plates encrusted with limestone under no electric current condition were higher than that of other conditions. In the field, the highest survival rates of juvenile corals occurred under the lowest electric current density. However, there was no difference on the growth of juvenile corals between different electric current levels. The mineral accretion could potentially be used to enhance survival of juvenile corals for coral rehabilitation purpose.